Continuous 3D printing by controlling the curing degree of hybrid UV curing resin polymer. (10th December 2021) - Kang, Xiaoqing; Li, Xiaogang; Li, Yuexuan; Zhang, Xiaohui; Duan, Yugang
Abstract: To achieve high speed and high efficiency continuous 3D printing, interface adhesion between the cured resin and the bottom of the resin tank has to be overcome and fast stripping has to be achieved. In this paper, a method that combines low surface energy Fluorine membrane and low curing degree hybrid resin is proposed to achieve continuous 3D printing. First, the mechanism of continuous printing was studied. Then, the effect of different ratios of cations and free radicals on the adhesion force was studied. Moreover, the curing degree was investigated. Finally, the accuracy and mechanical properties were tested. The results show that when the cationic content is 70% and the free radical content is 30%, the obtained adhesion force is the lowest, and mechanical properties, as well as surface quality of the printed samples, are optimal. More specifically, 540 mm/h printing speed, 2.9% low volume shrinkage, 61.37 MPa tensile strength, and 92.42 MPa bending strength can be achieved. The aforementioned can contributed to expanding the application of 3D printing. Graphical abstract: Image 1 Highlights: Continuous 3D printing can be achieved by combining Fluorine membrane and low curing degree hybrid resin. The cationic slow reaction reduces the curing degree of hybrid resin and the adhesion force are the main mechanism. With an increase in the cationic content, the adhesion force decreases. The appropriate cationic content is 70%. The mechanical properties and surface quality are improved when the cation content is 70%.